Cultivation of Water Spinach Using A Hydroponic Systems at Different AB Mix Concentrations - Vito Nanda, Chalen; Nur Khozin, Mohammad (University of Jember, 2022)
Water spinach is one of the most popular vegetable commodities in Indonesia. Currently, limited land due to plastic waste and uncertain climate change are inhibiting factors for plant cultivators. Efforts that can be done is to carry out cultivation activities to water spinach hydroponically. Hydroponic cultivation can use the wick system because it is easy to apply and does not require expensive costs. To support optimal growth of water spinach and reduce plastic waste in Indonesia, presenting AB Mix nutrition and the use of plastic bottles as a nutrient container in hydroponic cultivation are efforts to obtain quality water spinach production. This study aims to determine the response of water spinach plants to the use of hydroponic growing systems, as well as to obtain information regarding the best concentration of AB Mix. The experimental method used was a completely randomized design, which consisted of 3 levels, namely the nutrient concentration of 800 ppm, 1000 ppm and 1200 ppm. The results of the various concentrations of mixed AB showed significantly different effects on the parameters of plant height, number of leaves and weight of fresh plants. AB Mix concentration treatment of 1200 ppm was the best treatment for all observed parameters.